Acoustic wavefront manipulation via transmission-type labyrinth structure - Wang, Rui; Yang, Fengbao (Frontiers in Physics, 2022)
In this work, a transmission-type labyrinth structure (LS) is proposed to construct subwavelength acoustic functional metasurfaces, through which various desirable acoustic wavefront manipulation can be achieved in a broadband from 2700 Hz to 3900 Hz. By utilizing the excellent guiding property of LS, an invisibility cloak is designed to shield the target scattering body in the transmitted field. In addition, gradient metasurfaces composed of several LSs with different phase responses are constructed to obtain broadband beam deflection and focusing. Moreover, binary coding approach is adopted to further simplify the design philosophy of the metasurfaces by taking advantage of only two kinds of LS with opposite phase responses. Numerous wavefront manipulations including acoustic splitting beam and self-bending beam can be realized by using corresponding coding sequences. Our work provides a solution for multifunctional acoustic wavefront manipulation in a broadband, which may have potential applications in acoustic communication, detection and holography.